Systematic Literature Review: Students’ Challenges in Enhancing Reading Comprehension in Online Classrooms - Husna, Ayuri Rafikatul Husna; Istabana, Aly Ilham (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
While many studies have examined the challenges of online learning during the COVID-19 pandemic, but little focus has been focused on the unique challenges faced by students in enhancing their reading comprehension in online classrooms. The purpose of this study is to thoroughly examine the body of study findings in order to identify and define all of the challenges that students find, as well as to examine the strategies used to enhance reading comprehension skills in online classroom settings. This study investigated 15 peer-reviewed journal articles that were published between 2016 and 2025 using the Systematic Literature Review (SLR) method. The articles, which focused on studies involving EFL/ESL students in online or blended English language learning contexts, were chosen using particular inclusion and exclusion criteria. Thematic synthesis was utilized to analyze the data and classify recurrent issues. The results showed that students had a number of interconnected issues, such as a lack of motivation and self-control, a lack of interaction and feedback, a lack of digital literacy, and cognitive overload from multimedia content. Furthermore, socioeconomic factors like reliable internet access and suitable devices are also crucial. This study highlights the importance of interactive, scaffolded, student-centered reading activities. By focusing emphasis on the challenges associated with online reading, it supports educators, curriculum developers, and policymakers in enhancing online reading instruction.